P139 Prevalence of infections in patients affected by inflammatory bowel disease treated with anti-TNF-α agents: a single-centre experience. (15th January 2020) - Imperatore, N; Foggia, M; Rispo, A; Patturelli, M; Calabrese, G; Testa, A; Nardone, O; Pellegrini, L; Guarino, A D; Ricciolino, S; Tosone, G; Castiglione, F
Abstract: Background: Although the efficacy of anti-TNF α agents has dramatically changed the current management of inflammatory bowel disease (IBD), their safety represents an important issue in prescribing anti-TNF. In particular, anti-TNF α treatment has been associated with higher risk of developing infective disease, such as tuberculosis (TBC) and cytomegalovirus (CMV) reactivation and other viral/bacterial diseases. The aim of the present study was to evaluate the incidence and prevalence of CMV, TBC, hepatitis B (HBV) and C (HCV) infection/reactivation and other infections in IBD subjects treated with anti-TNF α. Methods: retrospective analysis of prospective maintained database including all IBD subjects treated with anti-TNF α (infliximab, adalimumab and golimumab) for at least 1 year in the period 2013–2018, whose infective serological status (Quantiferon TB test, Mantoux, CMV IgM/IgG, HBsAg, HBsAb, HBcAb, HBeAg, HBeAb, anti-HCV, anti-HIV, HSV IgM/IgG, VZV IgM/IgG, EBV IgM/IgG) was known before starting the treatment and during the follow-up. Incidence (number of infections per 100 patient-years) and prevalence of each infection was reported. Results: Among 689 who started an anti-TNF α agent, 288 subjects (males 52.8%, mean age 28.5 + 12.2 years, Crohn's disease 82.3%), met inclusion criteria and were enrolled. Total years/patient were 378.08 for infliximab, 627.58 for adalimumab and 8.25 for golimumab. Before starting treatment, CMV IgG antibodies were detectable in the majority (78.8%) of patients, but no case of IgM or CMV-DNA positivity was recorded; three subjects (1%) had latent TBC infection (LTBI) and were treated with isoniazide before starting anti-TNF; one case of HBV and one case of HCV infection were registered. During the anti-TNF α treatment, a total of 58 infective events (20.1%) were recorded: 63.8% during adalimumab and 36.2% during infliximab treatment. The most common infections were: urinary (34.5%), cutaneous (13.8%), HSV (13.8%), HPV (8.6%), upper respiratory infections (8.6%), gastroenteritis (6.9%), pneumonia (5.2%), bacteraemia (3.4%), VZV (3.4%) and de novo CMV (1.7%). Among them, 13 (22.4%) were considered severe, 11 (19%) needed hospitalisation and 9 (15.5%) led to anti-TNF withdrawal. No case of CMV or TBC reactivation was registered during the follow-up. The infection incidence rate was therefore 6.05/100 patient-years for adalimumab and 5.55/100 patient-years for infliximab ( p = NS) (Table 1). Conclusion: IBD patients are at high risk of developing infective disease during anti-TNF α therapy. The recognition of pre-exposure serological status, as well patients' strict monitoring during maintenance treatment, dramatically reduces the risk of severe reactivation (in particular TBC and CMV reactivation).